Real-world effects of Yishen Tongbi decoction for rheumatoid arthritis: protocol for a prospective, observational, multicenter cohort study with validation against double-blind, randomized, controlled trial - Liu, Lijuan; Zhu, Fangfang; Xin, Yijun; Zhang, Lu; Hu, Congqi; Xu, Yanping; Zhang, Jinming; Liu, Lingjie; Chen, Guangxing (Frontiers in Pharmacology, 2024)
Introduction: Rheumatoid arthritis (RA) is a globally challenging and refractory autoimmune disease, constituting a serious menace to human health. RA is characterized by recurrent pain and is difficult to resolve, necessitating prolonged medication for control. Yishen Tongbi decoction is a traditional Chinese herbal compound prescribed for treating RA. We have completed a 3-year RCT study that confirmed the clinical efficacy of Yishen Tongbi decoction for RA. Notably, we observed a faster clinical remission rate compared to MTX by week 4 of treatment. In our forthcoming study, we intend to conduct a comprehensive assessment of the efficacy and safety of Yishen Tongbi decoction in the real-world treatment of RA through a prospective study. Methods and analysis: This prospective, multicenter, real-world observational study will be conducted at two designated centers in China from October 2023 to August 2025. The study will include 324 patients with active rheumatoid arthritis. One group will receive Yishen Tongbi decoction combined with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs). The other group will receive standard treatment. Standard treatment can be further divided into subgroups: csDMARDs, targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), and biologic disease-modifying antirheumatic drugs (bDMARDs). In each group, the number of tender joints, number of swollen joints, pain score, patient global assessment, physician global assessment, disease activity index (DAS28-ESR or DAS28-CRP), clinical disease activity index (cDAI), simplified disease activity index (sDAI) and relevant laboratory data will be compared. Clinical indicators and disease activity of the patients will be assessed at baseline, week 4 and week 12 after the initiation of treatment. The primary outcome will be the American College of Rheumatology 20% improvement criteria (ACR20) attainment rate among patients at week 12 after treatment. Every adverse event will be reported. Ethics and dissemination: This study has been approved by the Ethics Committee of the first affiliated Hospital of Guangzhou University of traditional Chinese Medicine (NO.K-2023-009). The results of the study will be published in national and international peer-reviewed journals and at scientific conferences. The researchers will inform participants and other RA patients of the results through health education. Clinical Trial Registration:https://www.chictr.org.cn/index.html, identifier ChiCTR2300076073